Development of an autochthonous starter culture for spreadable goat cheese - Frau, Silvia Florencia (2016)
The aim of this work was to select strains of LAB autochthonous from Santiago del Estero to formulate a starter culture for making spreadable goat cheese. Four strains were selected: CRL1799 (Lactobacillus fermentum with high acidifying activity), CRL1803 (Lactobacillus fermentum with high proteolytic activity), CRL1808 (Lactobacillus rhamnosus with production of exopolysaccharide) and CRL1785 (Enterococcus faecium with diacetyl-acetoin production). The selected strains showed qualities that make them useful as starter culture in the elaboration of spreadable cheese. This starter culture is an alternative that allows obtaining differentiated products. The inclusion of CRL1808 strains seems to improve the rheology and texture, excluding the use of additives.